Implementation and evaluation of a multi-professional care pathway and network for the promotion of needs-oriented, resident-oriented exercise therapy for oncological patients (MOVE-ONKO): protocol of a mixed-methods cohort study - Blütgen, Saskia; Krug, Katja; Graf, Katharina; Betz, Ulrich; Böhm, Julian; Jäger, Elke; Krell, Verena; Müller, Jana; Pahl, Antonia; Voland, Annelie; Weigmann-Faßbender, Sandra; Zinkevich, Anna; et al. (BMC cancer, 2025)
Background: Physical activity has been shown to be beneficial for people diagnosed with cancer. MOVE-ONKO aims at implementing a new multiprofessional care pathway in 3 large regions in Germany at the interface of oncological treatment and exercise therapy for cancer patients. The related study aims to evaluate the implementation processes and patient outcomes. Methods: The project comprises 3 phases: 1) preparation, 2) implementation in Comprehensive Cancer Centres (CCCs), 3) implementation in remote cancer centres. In phase 1, individual prerequisites for the implementation are assessed in the participating CCCs. The care pathway which is supported by digital/app-based exercise oncology health record is developed and adapted to the CCCs. Phases 2 and 3 focus on the implementation and evaluation of the care pathway. To study the effectiveness, primarily changes in patients' health-related quality of life are examined in a prospective design. Secondary outcomes include physical activity behaviour, motivation for physical activity and patient activation. A sample of 2240 cancer patients ≥ 18 years (n = 280 patients at seven CCCs in phase 2 and n = 1.960 patients at the seven CCCs and 49 remote oncological centres in phase 3) are recruited for assessment at inclusion and at 4, 12 and 24 weeks. The newly implemented care structures and processes will be assessed from the perspective of key informants, healthcare providers and patients. The perspectives of key informants on the implementation from the CCCs will be recorded in a prospective design based on a questionnaire and supplemented by in-depth semi-structured interviews across the three phases. The implementation processes are documented by assessing existing structures in CCCs. In phase 2 (n = 105) and phase 3 (n = 350), healthcare providers will be surveyed with questionnaires. Based on purposeful sampling (n = 18) will be interviewed. Additionally, qualitative patient interviews will be conducted about their experiences in the care pathway. Discussion: A successful implementation of the care pathway as part of the study will contribute to the growing evidence on the implementation of a nationwide structured approach to exercise therapy for patients with cancer. Trial registration: ClinicalTrials.gov (ClinicalTrials Identifier NCT06185777) at December 29, 2023.
Gesehen am 09.09.2025